Post Injection Peripheral Nerve Injury and it's Managemen - Shahid Nawaz, Sarah Rehman, Raza Hassan, Sanaullah Pathan, Mubarak Hussain, Naseer Hassan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aimed to share our experience in treating various types of injection-induced peripheral nerve injuries and explore numerous problems that are related to this category of peripheral nerve injuries. Study Design: Retrospective study Place and Duration: Department of Neurosurgery, Gomal Medical College DI Khan in the duration from October, 2022 to March, 2023. Methods: Total 130 patients of both gender with age 8-70 years were included. Patients with post-operative peripheral nerve injuries were following intramuscular injections, brachial nerves block procedures, subclavian and jugular venous cannulation procedures for central line placements, and routine intravenous injections in the peripheral veins of the limbs. Frequency of peripheral nerve injuries and its management among all cases were assessed. SPSS 22.0 was used to analyze all data. Results: In all 130 patients, 82 (63.1%) cases were males and 48 (36.9%) patients were females. 45 (34.6%) patients had age 8-15 years, 30 (23.1%) cases had age 16-25 years, 33 (25.4%) cases had age 26-35 years and 22 (16.9%) patients had age >35 years. Mean duration of peripheral nerve injury was 2.4±7.38 months. Most common reason was intramuscular injection found in 104 (80%) cases. Most common affected nerve was sciatic nerve in the gluteal region, the radial nerve in the arm and axillary nerve in the shoulder region. Non-functional status among all cases were found in 58 (44.6%) cases. Six (4.6%) of the patients in our series experienced neurological impairment following surgery in the form of motor weakness. The best outcomes, 115 (88.5%), were reported with the repair of the radial nerve after surgery. Conclusion: We came to the conclusion that a quick referral to a specialized peripheral nerve center, an early intervention, and early diagnosis are just a few crucial elements that can lead to a positive outcome and reduce the frequency of medicolegal lawsuits. By having in-depth anatomical understanding and providing patients with adequate counseling before to the treatment, the problem can be avoided in the vast majority of cases. Keywords: Peripheral nerve injury, Surgery, Improvement, Injection